Network Communication Security: Challenges and Solutions in the Digital Era - Ashley Martinez; Arabella Fitzroy; Ainsley Hogwart (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2024)
Network communication security is basic within the advanced age due to the developing dependence on associated gadgets and computerized innovation. This theoretical investigates the issues of the computerized time whereas analyzing issues and potential answers in this subject. It offers a rundown of security dangers and shortcomings in a few sorts of systems, counting remote, arrange cutting, and in-automobile systems. It moreover looks at machine learning and cryptography strategies for making dependable security arrangements. Furthermore, the paper offers cures for imperative security imperfections and deterrents in IoT shrewd domestic advances.The challenges in arrange communication security are various and complex. These challenges incorporate the complexity of arrange situations, advancing risk scenes, information protection and compliance, bequest frameworks integration, client mindfulness and preparing, versatility, asset imperatives, and occurrence reaction. To address these challenges, inventive arrangements are required. One approach is to embrace a all encompassing approach to arrange security, which includes considering the whole arrange foundation and actualizing security measures at each layer. This incorporates actualizing strong get to controls, such as multi-factor confirmation and role-based get to control, to guarantee that as it were authorized clients can get to arrange resources. Encryption is another pivotal component of organize security, because it secures information in travel and at rest from unauthorized get to. Data loss avoidance instruments, such as information concealing and tokenization, can moreover offer assistance anticipate delicate information from being spilled or stolen.